Exploring Lessons from Soviet Diplomacy and Western Allied Cooperation in World War II - V. O. Pechatnov (Vestnik MGIMO-Universiteta)
Based on an analysis of documentary sources from Russian, American, and British archives, this article delves into the intricacies of coalition diplomacy among the Allies during World War II. It places special emphasis on the adherence to obligations and coalition behavior norms, encompassing respect for partners' interests, maintaining unity amidst divergences, coordinating actions towards shared objectives, and avoiding actions that risk coalition breakdown. The comparative analysis of Soviet and Anglo-American diplomacy reveals that the principal members of the anti-Hitler coalition generally adhered to these norms, contributing to the ultimate defeat of their common adversary. However, the study indicates that the Soviet Union exhibited greater fidelity in fulfilling its obligations and was more proactive in institutionalizing the coalition for enhanced stability and equal participation in strategic decision-making for war conduct and postwar arrangements. This quest for parity was often impeded by the Western powers' reluctance to accept the Soviet Union as an enduring, equal partner and legitimate member of the great powers' club, both during and after the war. This hesitance, the article argues, was rooted not just in geopolitical considerations but also in deep-seated cultural factors, particularly the traditional Western sense of superiority and perception of Russia as a 'lesser' civilization not fit for inclusion in the Euro-Atlantic community. The article brings to light lesser-known documents from US and UK archives to illustrate this mindset. It also acknowledges dissenting voices in Anglo-American political spheres who advocated for a more equitable relationship with the USSR. However, these perspectives did not significantly alter the overarching direction of Western policy.